Managing Cloud Technology Issues in Healthcare Management Organizations - Mohamed Doheir, Abd Samad Hasan Basari, Abdelrafe Elzamly, Noorayisahbe Mohd Yaacob ,Muath Jarrah , Samer Ali Al-shami (International Journal of Advanced Science and Technology, 2020)
Despite the huge benefits of cloud computing, they are associated with cloud issues in health care organizations. The aim of this paper is to manage cloud technology issues of healthcare management.   However, we  used the forward  regression algorithm to select the cloud  issues for improving healthcare management environments.  Indeed, the fact, all the cloud computing technology issues   are high and all the methods and solutions are   used most of the time. Table 28  shows the cloud computing issues identification checklist with methods and solutions based on experienced IT managers and developers  by using the forward regression models. In the future, we will create new cloud computing risk management based on intelligent methods. A successful cloud computing management will greatly improve the probability of cloud computing success in healthcare organizations.